Science Product Pipelines and Archive Architecture for the DART Mission - C. Dany Waller; Raymond C. Espiritu; Calley Tinsman; Hari Nair; Carolyn M. Ernst; R. Terik Daly; Olivier S. Barnouin; Angelo Zinzi; Nancy L. Chabot; Andrew S. Rivkin; Nicholas Moskovitz; David Osip; et al. (The Planetary Science Journal, 2024)
On 2022 September 26, the Double Asteroid Redirection Test (DART) mission was the first successful demonstration of a kinetic impactor for planetary defense. The DART mission utilized a novel autonomous data processing pipeline architecture to quickly produce and analyze the quality of raw and calibrated images from the camera mounted on board the spacecraft. Optimization of the data processing pipeline allowed the final 150 images prior to impact to be calibrated and delivered to the Investigation Team and the press within 15 minutes of acquisition. A data quality analysis pipeline allowed for rapid identification of detector misconfigurations, missing data, and other adverse events. DART data products, along with data from LICIACube and data from ground observatories, used common file formats to facilitate the development of analysis and archiving software. This architecture is described for future missions with large volumes of data and an emphasis on quick-turnaround applications such as planetary defense.